2006
DOI: 10.1093/nar/gkl338
|View full text |Cite
|
Sign up to set email alerts
|

The tale beyond the tail: histone core domain modifications and the regulation of chromatin structure

Abstract: Histone post-translational modifications occur, not only in the N-terminal tail domains, but also in the core domains. While modifications in the N-terminal tail function largely through the regulation of the binding of non-histone proteins to chromatin, based on their location in the nucleosome, core domain modifications may also function through distinct mechanisms involving structural alterations to the nucleosome. This article reviews the recent developments in regards to these novel histone modifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 107 publications
3
143
0
4
Order By: Relevance
“…15,16 This list is very likely to be growing in the near future given that mass spectrometry approaches have identified numerous novel histone modifications, whose roles are still to be determined. 18 While some modifications like H2AX phosphorylation (gH2AX) are induced by DNA damage, 19 others are normally cell-cycle regulated but persist after damage, as recently shown for H3K56 acetylation in yeast. 20 Finally, constitutive modifications can also provide specific binding sites for DNA damage response proteins, as described for methylation of H4K20 in fission yeast, 21 H3K79 in budding yeast 22,23 and both H3K79 and H4K20 in higher eukaryotes, 24,25 where determination of the relevant methylation site is still a matter of debate.…”
Section: Chromatin Rearrangements Crosstalk With the Dna Damage Responsementioning
confidence: 93%
“…15,16 This list is very likely to be growing in the near future given that mass spectrometry approaches have identified numerous novel histone modifications, whose roles are still to be determined. 18 While some modifications like H2AX phosphorylation (gH2AX) are induced by DNA damage, 19 others are normally cell-cycle regulated but persist after damage, as recently shown for H3K56 acetylation in yeast. 20 Finally, constitutive modifications can also provide specific binding sites for DNA damage response proteins, as described for methylation of H4K20 in fission yeast, 21 H3K79 in budding yeast 22,23 and both H3K79 and H4K20 in higher eukaryotes, 24,25 where determination of the relevant methylation site is still a matter of debate.…”
Section: Chromatin Rearrangements Crosstalk With the Dna Damage Responsementioning
confidence: 93%
“…Based on this interpretation, the biotin attachment sites were located predominantly in the N-terminal tail, specifically at lysines 5, 9, 13, or 15. Lysine 36, a residue within the globular domain of H2A on the lateral surface of the protein, 24 was also found to be biotinylated in the first hour of incubation. Interestingly, a lysine from the linker region connecting the His-tag to the native protein (labeled as position À5 in Table I) also showed a biotin attachment.…”
Section: Localization Of Nonenzymatic Biotin Attachment Sitesmentioning
confidence: 98%
“…This has led to the discovery of a myriad of novel histone modifications, many of which have yet to be ascribed a biological function. 1,2 Six independent research groups recently reported the discovery of lysine 56 as a novel site of histone H3 acetylation in the budding yeast Saccharomyces cerevisiae. [3][4][5][6][7][8] K56 acetylation has also been observed in the fission yeast Schizosaccharomyces pombe, 6 which is evolutionarily very distant from S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%